2000
DOI: 10.1034/j.1600-051x.2000.027001030.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of scaling and root planing on the clinical and microbiological parameters of periodontal diseases: 12‐month results

Abstract: The data suggest that the maintenance phase of therapy may be essential in consolidating clinical and microbiological improvements achieved as a result of initial therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

29
242
6
24

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 287 publications
(301 citation statements)
references
References 15 publications
29
242
6
24
Order By: Relevance
“…This study found a similar correlation with the previous studies where they found as positive correlation between CRP and periodontitis patients. [6][7][8] In this study, we observed a significant improvement in gingival score and plaque score following scaling and root planing (SRP), as documented in previous study 9 and also this study correlates with the previous study conducted and found a significant decrease in serum CRP, but only after a period of 6 months. 10 Observational nonexperimental studies have found similar …”
Section: Discussionsupporting
confidence: 80%
“…This study found a similar correlation with the previous studies where they found as positive correlation between CRP and periodontitis patients. [6][7][8] In this study, we observed a significant improvement in gingival score and plaque score following scaling and root planing (SRP), as documented in previous study 9 and also this study correlates with the previous study conducted and found a significant decrease in serum CRP, but only after a period of 6 months. 10 Observational nonexperimental studies have found similar …”
Section: Discussionsupporting
confidence: 80%
“…El nuevo crecimiento y recolonización de las bolsas ocurre 3-7 días posttratamiento, pero con una clara alteración en la microflora subgingival (24). Los colonizadores primarios de la placa dental con frecuencia ocupan las bolsas periodontales más rápido, inhibiendo así el establecimiento de otras especies patógenas (25). Esto puede explicar por qué en este estudio hay más localizaciones infectadas por 1 ó 2 especies después de la terapia, mientras que la mayoría de las localizaciones albergan 3 ó 4 especies antes del tratamiento.…”
Section: Discussionunclassified
“…The beneficial effects of scaling and root planing are based on a reduced mass of bacteria in the periodontal pockets (6) and a shift towards a less pathogenic microflora (9). During recent years, the effects of combining scaling and root planing with non-mechanical therapies have been evaluated (7).…”
Section: Role Of Hyaluronic Acid In the Treatment Of Periodontitismentioning
confidence: 99%